If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n(2n + 5p + -16) = 0 Reorder the terms: 3n(-16 + 2n + 5p) = 0 (-16 * 3n + 2n * 3n + 5p * 3n) = 0 Reorder the terms: (-48n + 15np + 6n2) = 0 (-48n + 15np + 6n2) = 0 Solving -48n + 15np + 6n2 = 0 Solving for variable 'n'. Factor out the Greatest Common Factor (GCF), '3n'. 3n(-16 + 5p + 2n) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0Subproblem 2
Set the factor '(-16 + 5p + 2n)' equal to zero and attempt to solve: Simplifying -16 + 5p + 2n = 0 Reorder the terms: -16 + 2n + 5p = 0 Solving -16 + 2n + 5p = 0 Move all terms containing n to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 2n + 16 + 5p = 0 + 16 Reorder the terms: -16 + 16 + 2n + 5p = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 2n + 5p = 0 + 16 2n + 5p = 0 + 16 Combine like terms: 0 + 16 = 16 2n + 5p = 16 Add '-5p' to each side of the equation. 2n + 5p + -5p = 16 + -5p Combine like terms: 5p + -5p = 0 2n + 0 = 16 + -5p 2n = 16 + -5p Divide each side by '2'. n = 8 + -2.5p Simplifying n = 8 + -2.5pSolution
n = {0, 8 + -2.5p}
| 4(2x-9)-2=4(x-4)+2 | | 8x-7=9x+15 | | -6X-2=3X^2+1 | | -116=4(1-7x)+4x | | 20(y+3)=4(3y+5) | | 4b-b=-99 | | 2(2.3x-3)=-5.494 | | 4(7m-5)= | | 5(5x-1)=75 | | 3(5x-1)=30 | | v(v-7)+v(6v+4)= | | 6x+17-5x=-2-10 | | -138=-6(3n+2) | | -4(2p+2)-30=2(5p+8) | | x^2+16x-42=0 | | 9x+5x-12x= | | 18+6g-12g=0 | | 145=15(x-75)+70 | | 9x+8x=6 | | 8n=3n+45 | | x+5y=6 | | -10b-6=5b-81 | | x*(x+2)=5x | | 5(8-4p)=160 | | 5-x=2x+5 | | 3x-14+2x+9=90 | | x*x+3x=40 | | 5x-18=4x+7 | | -2a-a=-7/2 | | 3(x+2)=7x+2-4x+4 | | 8a-35=a+14 | | 5-y=16 |